ANALISIS PERSEPSI MASYARAKAT ATAS DAMPAK PENGELOLAAN ALOKASI DANA DESA, PARTISIPASI MASYARAKAT, DAN KEBIJAKAN DESA TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT - Ihsan Zubaidi; Hardiwinoto Hardiwinoto; Ayu Noviani Hanum; Andwiani Sinarasri (Universitas Muhammadiyah Semarang, 2025)
The purpose of this study was to determine the influence of financial management of village fund allocation, community participation and village policies on improving the welfare of the people of Tersobo Village, Prembun District, Kebumen Regency. This study is a quantitative study using 97 samples. The data collection method used a questionnaire. Data analysis used multiple linear regression analysis. The results showed that Village Fund Allocation had a significant positive effect on Community Welfare with a t-count of 2.671> 1.986. Community Participation had a significant positive effect on Improving Community Welfare with a t-count of 2.100> 1.986. Village Policy had a significant positive effect on Community Welfare with a t-count of 8.409> 1.986.